An An Integrated Risk Management Approach to Delay Risk in the Procurement Project of an Accommodation Work Barge Using FMEA Method - Elga Madani Hanira; Chaerul D. Djakman (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to evaluate and design a risk management approach to address delay risks in the procurement project of an Accommodation Work Barge (AWB) at PT XYZ, a maritime company supporting the national oil and gas industry. The research applies the Failure Mode and Effects Analysis (FMEA) method integrated with the principles of ISO 31000:2018, using a qualitative case study approach. Data were collected through in-depth interviews, field observations, open-ended questionnaires, and project documentation. The results identified 18 potential risks across various project stages, from planning to execution. These risks were classified into three priority levels based on their Risk Priority Number (RPN): high priority (RPN > 200), medium priority (100 < RPN ? 200), and low priority (RPN ? 100). The highest-ranked risks included delays in the delivery of critical equipment, failure in coordination with external vendors, and weak oversight in vessel quality inspection procedures. Proposed mitigation measures include strengthening logistical control, implementing performance-based vendor evaluation, and enhancing technical SOPs and interdepartmental communication. This research contributes by providing an evaluative framework that can be utilized by similar companies to systematically identify, assess, and mitigate project risks. The recommendations aim to support the efficiency of procurement processes and reduce the likelihood of delays that may impact financial and operational performance.